Hamstring stiffness and injury risk factors during the handball season in female players - Satkunskiene, D.; Skarbalius, A.; Kniubaite, A.; Mickevicius, M.; Snieckus, A.; Rutkauskas, S.; Kamandulis, S. (Applied Physiology, Nutrition, and Metabolism, 2024)
Monitoring the muscle mechanical properties and functions of female athletes throughout their training season is relevant to understand the relationships between these factors and to predict noncontact injuries, which are prevalent among female athletes. The first aim of this study was to determine whether female handball players` passive stiffness of the hamstring muscles is associated with hamstring extensibility, strength of knee flexors and extensors, and lower limb stiffness. Additionally, the study monitored fluctuations in these factors over 25 weeks. The study utilized an isokinetic dynamometer to record hamstring passive stiffness, extensibility, and hamstring and quadriceps strength of 18 young handball players. Lower limb stiffness was determined from a countermovement vertical jump conducted on a force plate. The countermovement jump involved the calculation of the peak force during the eccentric phase and the mean force during the concentric phase. The results showed a positive correlation between hamstring passive stiffness and lower limb stiffness (r = 0.660, p < 0.01), knee flexion and extension strength (r = 0.592, p < 0.01 and r = 0.497, p < 0.05, respectively), and eccentric peak force (r = 0.587, p < 0.01) during jumping. The strength of knee extensors increased significantly after 6 weeks, and hamstring stiffness after 12 weeks of training. In conclusion, the increased hamstring stiffness following training did not match other factors associated with injury risk. Therefore, preventing multifactorial injury risk requires a comprehensive approach, and monitoring one factor alone is insufficient to predict noncontact injuries in female handball players.